Immunogenic salivary proteins of Triatoma infestans: development of a recombinant antigen for the detection of low-level infestation of triatomines. - Alexandra Schwarz; Stefan Helling; Nicolas Collin; Clarissa R Teixeira; Nora Medrano-Mercado; Jen C C Hume; Teresa C Assumpção; Katrin Marcus; Christian Stephan; Helmut E Meyer; José M C Ribeiro; Peter F Billingsley; et al. (Public Library of Science (PLoS), 2009)
Triatomines are vectors of Trypanosoma cruzi, the etiological agent of Chagas disease in Latin America. The most effective vector, Triatoma infestans, has been controlled successfully in much of Latin America using insecticide spraying. Though rarely undertaken, surveillance programs are necessary in order to identify new infestations and estimate the intensity of triatomine bug infestations in domestic and peridomestic habitats. Since hosts exposed to triatomines develop immune responses to salivary antigens, these responses can be evaluated for their usefulness as epidemiological markers to detect infestations of T. infestans.T. infestans salivary proteins were separated by 2D-gel electrophoresis and tested for their immunogenicity by Western blotting using sera from chickens and guinea pigs experimentally exposed to T. infestans. From five highly immunogenic protein spots, eight salivary proteins were identified by nano liquid chromatography-electrospray ionization-tandem mass spectrometry (nanoLC-ESI-MS/MS) and comparison to the protein sequences of the National Center for Biotechnology Information (NCBI) database and expressed sequence tags of a unidirectionally cloned salivary gland cDNA library from T. infestans combined with the NCBI yeast protein sub-database. The 14.6 kDa salivary protein [gi|149689094] was produced as recombinant protein (rTiSP14.6) in a mammalian cell expression system and recognized by all animal sera. The specificity of rTiSP14.6 was confirmed by the lack of reactivity to anti-mosquito and anti-sand fly saliva antibodies. However, rTiSP14.6 was recognized by sera from chickens exposed to four other triatomine species, Triatoma brasiliensis, T. sordida, Rhodnius prolixus, and Panstrongylus megistus and by sera of chickens from an endemic area of T. infestans and Chagas disease in Bolivia.The recombinant rTiSP14.6 is a suitable and promising epidemiological marker for detecting the presence of small numbers of different species of triatomines and could be developed for use as a new tool in surveillance programs, especially to corroborate vector elimination in Chagas disease vector control campaigns.